2019
DOI: 10.3390/agronomy9070388
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Improves the Production of High Antioxidant or Structural Phenolic Compounds in Barley Cultivars under Aluminum Stress

Abstract: Aluminum (Al) toxicity is one of the main growth and yield limiting factors for barley grown on acid soils. Silicon (Si) ameliorates Al toxicity as well as it promotes the phenolic compounds production that have antioxidant or structural role. We evaluated the time-dependent kinetics of Al and Si uptake and the impact of Si on the production of antioxidant- or structural- phenols in barley cultivars at the short-term. Two barley cultivars with contrasting Al tolerance (Hordeum vulgare ‘Sebastian’, Al tolerant;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 70 publications
13
33
0
2
Order By: Relevance
“…The remarkable increases in NPK was recorded in the current research due to Si+ proline application, this increase might be due to the role of Si in improving membrane H ± ATPase activity which enhances element uptake, mainly K + and Ca + and improve photosynthesis and water relations [ 83 ]. The helpful impact of Si on nutrient content was observed in some plants [ 8 , 42 ] and that could be explained by the regulation of key enzyme activity in the phenylpropanoid pathway [ 84 ] and the improvement of total phenol formation [ 85 ]. The role of proline in increasing NPK content under drought could be due to that proline is an amino acid and involved in increase plant tolerance to stresses by enhancement plant metabolism as well as increase nutrients uptake [ 86 ] as well as increase energy production in the electron transport chain and ATP synthesis [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable increases in NPK was recorded in the current research due to Si+ proline application, this increase might be due to the role of Si in improving membrane H ± ATPase activity which enhances element uptake, mainly K + and Ca + and improve photosynthesis and water relations [ 83 ]. The helpful impact of Si on nutrient content was observed in some plants [ 8 , 42 ] and that could be explained by the regulation of key enzyme activity in the phenylpropanoid pathway [ 84 ] and the improvement of total phenol formation [ 85 ]. The role of proline in increasing NPK content under drought could be due to that proline is an amino acid and involved in increase plant tolerance to stresses by enhancement plant metabolism as well as increase nutrients uptake [ 86 ] as well as increase energy production in the electron transport chain and ATP synthesis [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that silicon promotes the production of phenolic compounds that have an antioxidant or structural role. In addition, it can improve toxicity to heavy metals such as aluminum [77].…”
Section: Discussionmentioning
confidence: 99%
“…However, in acid soils, barley growth is limited due to its high sensitivity to Al 3+ , which reduces both the yield and quality of the grains. In this context, some reports have demonstrated an improvement in the Al tolerance of barley following Si addition [17,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been suggested that Si can alter the secondary metabolism of plants [2,[11][12][13][14]. In this regard, Si appears to stimulate the production of phenols in plants subjected to salinity, drought, temperature stress, UV radiation, cadmium, chromium [2], manganese [15], aluminum [16,17], nickel [11], soil acidity [18] and biotic [12,19,20] stresses. There is some evidence showing that the positive effects of Si on phenol metabolism in plants growing in stressful environments is due to (i) the regulation of the gene expression or activity of key enzymes in the phenylpropanoid pathway [21,22], (ii) the enhancement of total phenol production [17,23], and/or (iii) the formation of complexes involving lignin and carbohydrates [24,25] or Si-polyphenol in the cell wall [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation